SINKRONISASI AKUNTANSI PENERIMAAN PAJAK HOTEL DAN RESTORAN DENGAN PERATURAN PERUNDANG-UNDANGAN - Dayanti, Eva Nur Fri; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out how the accounting of revenue Hotel tax and Restaurant tax in Sidoarjo district and to find out how big its contribution to the Local Own-Source Revenue in Sidoarjo district. The research object is the tax revenue of Hotels and Restaurants in Sidoarjo district in the budget years from 2011 to 2013. This research is descriptive qualitative research. The data is the primary and secondary data which means that the data has been obtained directly and indirectlyby performing direct observation and conducting interview to the related parties as well as documents, archives, records, and historical statements which have been organized in the archive of Revenue Service of Sidoarjo District. The financial accounting of Sidoarjo district, in recording and reporting of Hotel and Restaurant tax revenue during the observation years is in accordance with the provision of Regent regulation No. 62 of 2012 about the amendment of Sidoarjo Regent regulation No. 50 of 2009 about the Accounting Policy on the Department of Finance, Revenue Management, and Assets Sidoarjo district. Keywords : Accounting of Tax Revenue, Regent Regulations, and Accounting Policy.